(untitled) (Medical Forum Monthly, 2024)
Objective; To determine frequency of BCG Vaccination in patients of tuberculous meningitis presenting at a tertiary care hospital. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Pediatric Medicine, Services Hospital Lahore from June 2016 to June 2017. Materials and Methods; A total of 167 Patients were included in the study. Patients with Tuberculous meningitis (TBM) less than 5 years of age were included. Patients having acute onset of encephalopathy and those with lumbar puncture contraindicated were excluded from our study. Demographic bio data (patient name, father name, age, gender, date of admission) was taken. After that complete history regarding presenting complaints and vaccination were taken. Physical examination will be done. BCG scar ark was identified on examination. CSF examination, Chest X-ray, CT scan brain was done from single laboratory. Tuberculin test was applied and interpreted by experience pediatrician. Data was recorded on the specifically designed proforma. Results; Of these 167 study cases, 106 (63.5%) were boys while 61 (36.5%) were girls. Mean age of our study cases was 3.31 ± 0.98 years. Mean duration of disease was noted to be 4.71 ± 1.49 weeks. History of contact with index TB patients was positive in 114 (68.3%) of our study cases, 68 (40.7%) were from rural areas and 99 (59.3%) from urban areas and majority of them i.e. 90 (53.9%) belonged to poor families with majority of mothers i.e. 129 (77.2%) were uneducated. BCG vaccination was positive in 94 (56.3 %) of our study cases. Conclusion; Our study results support the use of BCG vaccination as it has some protective role against TB. Very high frequency of history of contact with positive index case was observed in our study. BCG vaccination was significantly associated with gender, history of contact with index case and socioeconomic status.